IoT based smart biofloc monitoring and maintenance system - Podder, Saurov; Anoy, Mohammad Fahim Sultan; Ahmed, Tausif; Jesan, Syed Nafew Hasan (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.